Miss Fisher's murder mysteries. [videorecording (DVD)] Series 3 - Davis, Essie; Page, Nathan, 1973-; Johnstone-Burt, Hugo; Greenwood, Kerry ([Publisher not identified], 2015)
Follow the Honorable Phryne (fry-nee) Fisher through the back alleys, shady markets, and jazz clubs of late 1920s Melbourne. A glamorous lady detective in a mostly male world, she goes about her work with a pear-handled pistol and dagger-sharp wit, leaving a trail of male admirers in her wake. Includes 8 episodes.